Rapid regression of microsatellite instability-high/programmed cell death ligand 1-negative recurrent endometrial carcinoma by immune checkpoint blockade with pembrolizumab: A case report and literature review - Akihiro Takeda; Wataru Koike; Kazuko Watanabe (Elsevier, 2020)
In a 53-year-old woman who had a surgical diagnosis of grade 3 endometrioid carcinoma (pT1aN0M0, FIGO 1A), adjuvant chemotherapy with paclitaxel and carboplatin was initiated. However, after the completion of fourth cycle, the patient refused to continue the treatment. At 12 months after surgery, local recurrence was noted near the left posterior portion of the vaginal stump. External radiotherapy to the pelvic cavity achieved marked reduction of the tumor. At 12 months after radiotherapy, regrowth of the tumor was noted. Although the tumor was negative for programmed cell death ligand 1, after the identification of a high level of microsatellite instability, treatment with pembrolizumab, an immune checkpoint inhibitor, was initiated. After 2 cycles of treatment, the recurrent tumor markedly regressed. Four months later, a complete metabolic response was confirmed by positron emission tomography, without any immune-related adverse events; at the time of writing, this has been maintained for 9 months.